Dedicated comparatives aid comparisons of magnitude: a study with Pitjantjatjara-English bilinguals - Greenacre, Luke; Defina, Rebecca; Akbar, Skye; Garcia, Jair E. (Frontiers in Human Neuroscience, 2024)
When expressing comparisons of magnitude, Pitjantjatjara, a language indigenous to the land now known as Australia, employs contextually driven comparators (e.g. Anyupa is tall. Uma is short) rather than a dedicated morphological or syntactic comparative construction (e.g. Anyupa is taller than Uma). Pitjantjatjara also has a small number of lexicalized numerals, employing ‘one’, ‘two’, ‘three’, then ‘many’. It is hypothesized that having dedicated comparatives in language and elaborated number systems aid comparisons of magnitudes. Fluent Pitjantjatjara-English bilinguals participated in tasks assessing their accuracy and reaction times when comparing two types of magnitude: numerosity (quantities of dots), and extent (line lengths). They repeated the comparisons in both languages on different days, allowing for the effect of language being spoken on responses to be assessed. No differences were found for numerosity; however, participants were less accurate when making comparisons of extent using Pitjantjatjara. Accuracy when using Pitjantjatjara decreased as the magnitude of the comparison increased and as differences between the comparators decreased. This result suggests a potential influence of linguistic comparison strategy on comparison behavior.